Proposta de instrumento diagnóstico para fornecer indicativos acerca da compreensão dos conhecimentos biológicos e suas inter-relações - Caldeira, Ana Maria de Andrade; Siebert, Paloma Rodrigues; Corrêa, André Luis; Meglhioratti, Fernanda Aparecida; Brando, Fernanda da Rocha; Maricato, Fúlvia Eloá; Justina, Lourdes Aparecida Della; de Andrade, Mariana Aparecida Bologna Soares; de Oliveira, Thais Benetti; Augusto, Thais Gimenez da Silva (Góndola, enseñanza y aprendizaje de las ciencias, 2016)
This paper describes the developing and validating steps of a Likert’s evaluative scale. The aim is to systematize the answers of Biological Sciences students about to: 1) Understanding or notunderstanding thescientific knowledge; and 2).If there is a relationship amongscientific concepts in order to contemplate a systemic thinking about natural phenomena. The described scale was validated by Cronbach's Alpha tests (α = 0.741), KMO (0.779) and Bartlett (0.000) and a Multivariate Analysis was fulfilled, typePrincipal Component Analysis (PCA). We understood that this kind of instrument allows a large amount of data to be collected and it groups can be compared efficiently, which justified the development of evaluative scale presented here.